2011
DOI: 10.5732/cjc.010.10344
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic significance of TCR gene clonal rearrangement analysis in early mycosis fungoides

Abstract: Mycosis fungoides (MF), the most common type of cutaneous T-cell lymphoma, has various unspecific clinical and histological characteristics. Its early diagnosis is challenging. The application of T-cell receptor (TCR) gene clonal rearrangement to the diagnosis of MF has been widely studied. In this study, we used polymerase chain reaction (PCR) to investigate the diagnostic significance of detecting TCR-γ and -β gene clonal rearrangement in the early diagnosis of mycosis fungoides. PCR for TCR-γ and TCR-β gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…In previous studies, clonal TCR ‐γ rearrangement was observed in 73% of cases in plaque stage and in 100% of cases in tumor stage 30,31 . In our analysis, 19 clonality was showed in 71.4% of cases in plaque stage and in 100% of cases in tumor stage by using conventional phenol‐chloroform DNA extraction and multiple PCR/heteroduplex analysis. The percentages obtained in our study were within the range reported by others 10–12,30,31 .…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…In previous studies, clonal TCR ‐γ rearrangement was observed in 73% of cases in plaque stage and in 100% of cases in tumor stage 30,31 . In our analysis, 19 clonality was showed in 71.4% of cases in plaque stage and in 100% of cases in tumor stage by using conventional phenol‐chloroform DNA extraction and multiple PCR/heteroduplex analysis. The percentages obtained in our study were within the range reported by others 10–12,30,31 .…”
Section: Discussionsupporting
confidence: 50%
“…The TCR ‐γ gene, although typically not expressed on the cell surface, remains rearranged in the T‐cell genome and is a suitable target for amplification mainly because its relatively simple structure requires fewer sets of PCR primers to detect the most common genes. In our previous study, 19 we used six different primer pairs (T VG /T JX , V 2–5 /V 8–12 /JGT 1 , V γ11 /V γ101 /J γ12 , V γ11 /V γ101 /J p12 , BIOMED‐2‐TCR‐γ and BIOMED‐2‐TCR‐β) to detect clonality in classic MF. On the basis of the results, 19 T VG /T JX , V 2–5 /V 8–12 /JGT 1 and BIOMED‐2‐TCR‐γ were selected and utilized in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T-cell clonality was present in about 70% (50% -100%) of the biopsies diagnosed as MF [30][31][32][33]; this was 28.5% in a study in Hong Kong [20]. In current study 61.1% of cases showed clonality.…”
Section: Discussionmentioning
confidence: 44%